Smart Materials for Ranging Systems - Franse, Jaap.; Eremenko, Victor; Sirenko, Valentyna; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The problem of determining the location of an object (usually called ranging) attracts at present much attention in different areas of applications, among them in ecological and safety devices. Electromagnetic waves along with sound waves are widely used for these purposes. Different aspects of materials with specific magnetic, electric and elastic properties are considered in view of potential application in the design and manufacturing of smart materials. Progress is reported in the fabrication and understanding of in-situ formation and characterization of solid state structures with specified properties. Attention is paid to the observation and study of the mobility of magnetic structures and of the kinetics of magnetic ordering transitions. Looking from a different perspective, one of the outcomes of the ARW is the emphasis on the important role that collective phenomena (like spin waves in systems with a magnetically ordered ground state, or critical currents in superconductors) could play at the design of magnetic-field sensitive sensor materials.
MAGNETIC DYNAMICS OF CO NANOSPHERES: ORIGIN OF THE ENHANCED ANISOTROPY -- NANOPARTICLES IN OXIDE GLASSES: MAGNETIC RESONANCE STUDIES -- EFFECT OF MAGNETIC FIELD ON THE MAGNETIC STATE OF COPPER METABORATE -- INTRINSICALLY INHOMOGENEOUS MAGNETIC STATES IN ANTIFERROMAGNETS -- NMR STUDYOFTHE SUCCESSIVE PHASE TRANSITIONS IN CuB2O4 -- MAGNETIC PROPERTIES OF CUPRATE PEROVSKITES -- QUANTUM CRITICAL PHENOMENA AND THE ANOMALOUS LOW-TEMPERATURE PROPERTIES OF THE U(Pt,Pd)3 SYSTEM -- THE PERIODIC ANDERSON MODEL IN THE GENERATING FUNCTIONAL APPROACH -- ORBITAL ORDERING AND PHASE SEPARATION PHENOMENA IN LIGHTLY DOPED MANGANITES -- INTERFACE AND MAGNETIC CHARACTERIZATION OF FM/AF/FM MULTILAYERS -- SQUID-BASED MAGNETIC MICROSCOPE -- FEMTOSECOND ELLIPSOMETRY: A NEW TOOL FOR THE MEASUREMENT OF HOT ELECTRON MOMENTUM RELAXATION TIMES IN METALS -- FERROMAGNETIC SHAPE MEMORY ALLOYS Ni2+xMn1?x Ga -- MAGNETOSTRICTION OF MANGANITES AND COBALTITES -- STRUCTURAL STUDY OF MAGNETOSTRICTIVE SUPERCONDUCTING COMPOUNDS.
Keywords: PHYSICS; CONDENSED MATTER; SUPERCONDUCTIVITY; MAGNETISM; PHYSICAL OPTICS; PHYSICS; CONDENSED MATTER; MAGNETISM, MAGNETIC MATERIALS; SUPERCONDUCTIVITY, SUPERFLUIDITY, QUANTUM FLUIDS; APPLIED OPTICS, OPTOELECTRONICS, OPTICAL DEVICES